Latihan Autogenik Meningkatkan Kualitas Hidup Klien Hipertensi - I Gusti Ayu Putu Desy Rohana; Gunardi Pome; Masayu Hartina Ulfa; D. Eka Harsanto; Muhamad Jauhar (JURNAL KEPERAWATAN RAFLESIA, 2023)
The quality of life of people with hypertension is influenced by a sense of comfort that arises from the symptoms of the disease. Autogenic exercise is a nursing intervention that is often used for hypertensive patients. Autogenic training is a type of psychophysiological psychotherapy that provides self-sourced suggestions of calm. This research aims to determine the effect of autogenic training on the quality of life of hypertensive patients. This research with a quasi-experimental design with control group with pretest and posttest types. The sample size in this study was 30 hypertension clients in each intervention and control group. The intervention provided was 5 sessions of Autogenic Training with an internalization period of 1 month of independent practice. Data collection using the WHOQOL-BREF questionnaire to measure the quality of life of hypertension patients. Statistical test results obtained a significant change in the quality of life with p-value=0,001 (p<0.005). The results showed a significant effect on the quality of life of the respondents after carrying out the autogenic exercise intervention. The results of the study are expected to be applied as an alternative to caring in improving the quality of life of hypertensive patients in the community.